Simulating Photosynthesis, Respiration and Dry Matter Production in Annual Crops - Sedghi, Raouf Seyed Sharifi, Amir Heydari, Abdolghayoum Gholipouri, Mohammad (Journal of Phytology, 2009)
Crop simulation model, mathematical exhibition of physiological different process of crop growth and development and its response to environmental factors. Then the aim ofÃ‚Â this study is to provide a computer model for simulating photosynthetic, respiration and dry matter production in annuls crop. In this model daily gross canopy photosynthetic rate is a fraction of the maximum photosynthetic rate of a fully developed canopy at light saturation. For calculation of that, leaf area index based on the relative length of the four different crop development stage is calculated. Leaf area index, minimum and maximum daily temperature and daily radiation as model inputs were considered. After calculating gross photosynthetic rate, growth and maintenance respiration waste minus its and daily dry matter is calculated based on conversion efficiency coefficient. Sunflower data is used for testing of model. Regression of simulated over observed dry matter yield and leaf area index showed a good correspondence between predicted and observed dry matter yield and leaf area index. R2Ã‚Â for bothÃ‚Â dry matter yield and leaf area index were more than 0.95 suggesting that the model was successful in growth and yield crop.